Optimizing the Use of Social Media and Digital Technology to Market Insurance Products and Services - Mulawarman Mulawarman; Robidi Robidi; I Nyoman Winata; Erizal Erizal (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to examine the ability of insurance marketers in insurance companies to develop selling methods on social media using a set of today's technologies. The social media used is Facebook. WhatsApp, LineApps and Youtube. While the devices used for testing are smartphones, mobile phones, laptops and tablet computers. Using the survey method, the results show that marketers access social media using laptops and smartphones. The most popular social media for promoting, marketing and selling insurance products and services is WhatsApp.